Emerging trends in government venture capital policies in smaller peripheral economies: Lessons from Finland, New Zealand, and Estonia. (13th January 2019) - Owen, Robyn; Mason, Colin
Abstract: Emerging trends from the developing venture capital industries of three smaller peripheral economies (Finland, New Zealand, and Estonia), demonstrate that government policy can overcome scale and distance barriers to assist in establishing venture capital to support innovative potential high growth ventures. Eight common policy themes for successful venture capital development are: new venture stimulation; dedicated finance policy institutions; stable, internationally harmonized tax and regulations; business angel development; inward investment; international venture capital fund development; smooth pipeline of investment; effective investment exit market. Venture capital policy development themes are interconnected, requiring a holistic ecosystem approach. A blueprint for successful small peripheral economy venture capital development requires an initial phase of new venture demand stimulation and ensuing simultaneity of policies to engineer venture capital development.